Activin A Inhibits Antigen-Induced Allergy in Murine Epicutaneous Sensitization - Kypriotou, Magdalini; Rivero, Dianelys; Haller, Sergio; Mariotto, Anita; Huber, Marcel; Acha-Orbea, Hans; Werner, Sabine; Hohl, Daniel (Frontiers in Immunology, 2013)
Activin A, a member of the TGFβ superfamily, is involved in physiological processes such as cell differentiation, tissue homeostasis, wound healing, reproduction, and in pathological conditions, such as fibrosis, cancer and asthma. Activin enhances mast cell maturation, as well as regulatory T-cell and Langerhans cell differentiation. In this study we investigated the potential role of activin in epicutaneous sensitization with ovalbumin, notably with respect to its effect on known Th2-polarisation. For this purpose, transgenic mice overexpressing activin in keratinocytes and their wild-type controls were sensitized epicutaneously with ovalbumin (OVA). Skin biopsies were analyzed with regard to histopathological features and mRNA expression of pro-inflammatory and Th1/Th2 cytokines, and Ig levels were measured in the serum. Unexpectedly, activin overexpressing animals were protected from Th2-cytokine expression and induction of OVA-specific IgE levels compared to WT animals. On the other hand, transgenic mice were more susceptible to inflammation compared to wild-type littermates after tape-stripping and saline (vehicle) or OVA application, as shown by increased pro-inflammatory cytokine mRNA levels and neutrophil accumulation at the site of the treatment. We conclude that activin protects from antigen-induced cutaneous Th2-polarization through modulation of the immune response. These findings highlight the role of activin in cutaneous sensitization, allergy and in skin homeostasis.